PUBLIC PROPERTY RIGHT AND ITS TYPES (British Journal of Global Ecology and Sustainable Development, 2024)
In this article, the concept of public property rights, its types, opinions given by scientists to the concept of public property, regulation of public property by laws, concepts of republican and municipal property and their essence, legal regulation of public property in foreign countries and regulation of public property in the legislation of the Republic of Uzbekistan the differences and similarities between the comparisons are explained.